Diagenesis of microbialite-dominated carbonates in the Upper Ediacaran Qigebrak Formation, NW Tarim Basin, China: Implications for reservoir development. (February 2022) - Tang, Pan; Chen, Daizhao; Wang, Yuanzheng; Ding, Yi; El-Shafeiy, Moataz; Yang, Bo
Abstract: The interests in deeply-buried hydrocarbon reservoirs increase rapidly with increasing performances into greater depths. The ancient Ediacaran Qigebrak Formation microbialites in Tarim Basin are widespread and increasingly considered as a potential hydrocarbon exploration target for deeply-buried carbonate reservoirs. However, controlling factors on the development of microbialite reservoirs have not well been understood yet. This work was conducted upon microbialites of the Qigebrak Formation, Aksu, NW Tarim Basin based on detailed petrological, geochemical, and petrophysical investigations, aiming at understanding the diagenetic processes and influences on the porosity generation and preservation. The investigated dolomicrobialites, encompass four distinctive lithofacies types: microbial laminite, stromatolite, spongiomicrobialite, and microbial-peloidal wackstone/packstone. The main diagenetic minerals consist of three types of dolomite (microbial dolomicrite, early-stage fibrous dolomite cement, and late-stage pore filling dolomite cement), quartz, calcite and bitumen fillings. Pore spaces are dominated by vugs, solution-enhanced pores, microbial framework pores, intercrystalline pores, micropores and fractures. Among all the microbialites, spongiomicrobialites have porosity averaging 6.15% and permeability averaging 0.20 mD, which show better petrophysical properties than other microbialites. This study pinpoints that the development of a high quality microbialite reservoir in the studied area was essentially controlled by three controlling factors: microbial mat deposition, early dolomitization, and meteoric karst leaching. Microbial mat deposits can be considered as the foundation to form framework pores. Furthermore, the early dolomitization increased the resistivity of the studied microbialites toward chemical and physical compaction, during which abundant micropores are generated. The meteoric karst dissolution, which is related to the uppermost Qigebrak Formation unconformity surface, is the crucial controlling factor that enhanced the porosity via forming a large quantity of vugs- and solution-related pores. This study attempts to better understand the microbialites diagenesis that may have affected the reservoir property, and to serve as an analog for the similar microbialite reservoirs in other areas of China. Highlights: Four types of microbialite lithofacies were recognized. Petrophysical properties of different microbialites were influenced by microbial fabrics. Microbial mat deposition, seawater dolomitization and meteoric karstification controlled reservoir formation. Meteoric karstification on the uppermost Ediacaran greatly improved the reservoir quality.